Fog node placement using multi-objective genetic algorithm - Singh, Satveer; Vidyarthi, Deo Prakash (International journal of information technology (Singapore. Online), 2024)
The emergence of the Internet of Things (IoT) has paved the way for numerous activities leading to smart life, such as health care, surveillance, and smart cities. Since many IoT applications are real-time, they need prompt processing and actuation. To enable this, a network of Fog devices has been developed to provide services close to the data generation points, i.e., the network's edge. Designing a feasible Fog network for managing the explosion of data from the edge to the Cloud requires intelligent monitoring. This work develops a model to address the issue of Fog node placement in a geographical area. The proposed model determines the location of the Fog devices and how to connect them to the Cloud in the best feasible way. Using a multi-objective genetic algorithm (MOGA), the proposed model minimizes the Deployment Cost (DC) and network latency (NL). The simulation setting is designed in Spyder (Anaconda3) using Python programming.